Prawne formy przeciwdziałania obejściu prawa podatkowego - Białowska, Aleksandra (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
Paying less tax is a concern for many taxpayers. In order to counteract this, legal regulations such as tax circumvention, tax avoidance, tax evasion or aggressive tax planning have been introduced. Controversy has arisen as to whether the tax authorities are entitled to make use of a civil institution such as the sham of a legal transaction. Three kinds of conflicting interests are involved: individual, social and state, as well as law and economics. The scope of the article covers the issue of legal forms of counteracting tax law circumvention, examining tax, civil and criminal law.
Keywords: tax law; tax circumvention; tax avoidance; tax optimization; tax saving; sham